Foams of vegetable oils containing long-chain triglycerides - Liu, Yu; Binks, Bernard P. (Journal of colloid and interface science, 2021)
[Display omitted] •Stable edible oil foams without added foaming agent.•Air bubbles coated by crystals of long-chain, unsaturated triglycerides.•Packing density of crystals at air bubble surfaces in oil depends on oil type.•Thermo-responsiveness of oil foams.•Chemical composition of high melting triglyceride crystals. Can vegetable oils containing long-chain triglycerides be aerated to yield stable oil foams? This is based on the idea that cooling of vegetable oil results in the formation of crystals of certain triglyceride chain lengths and composition dispersed in liquid oil of other chain lengths and composition. Do such oleogels allow the formation of oil foams stabilised by adsorbed crystals? Using two vegetable oils, the temperatures for crystal formation are determined. Crystal dispersions were characterised using rheology and optical microscopy. Oleogels were aerated using a double beater and the effects of temperature and aeration time were investigated. The stability and microstructure of the oil foams were studied visually and using microscopy. A stable oil foam was progressively destabilised on heating. Upon cooling/warming vegetable oils, crystals of high melting triglyceride form in a low melting liquid oil - an oleogel. Such oleogels can be whipped to fabricate oil foams stabilised by fat crystals. Optimum foaming yields an over-run of ~ 40% for peanut oil and ~ 110% for olive oil. Oil foams which do not exhibit drainage, coarsening or coalescence result. We show that high melting triglyceride crystals possess a higher fraction of saturated fatty acids than the original oil. Ultra-stable oil foams can be rendered unstable by heating upon approaching the melting point of the crystals.